The effect of work stress and work conflict and social support on nurse performance - Mardewi, Shinta; Tricahyadinata, Irsan (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2023)
This study aims to determine the effect of Work Stress, Work Conflict and Social Support on Nurse Performance. This research is quantitative in nature using data collection methods with questionnaires in the form of a google form link and hardcopy, using a simple random sampling technique. The sample of this study amounted to 60 respondents. The analysis method uses Structural Equation Modeling (SEM) with the Partial Least Square (PLS) version 3.0 approach. The results of this study indicate that work stress has a positive and significant effect on nurse performance, work conflict has a positive and significant effect on nurse performance, and social support has a positive and significant effect on nurse performance